Co-Loading of Inorganic Nanoparticles and Natural Oil in the Electrospun Janus Nanofibers for a Synergetic Antibacterial Effect - Menglong Wang; Deng-Guang Yu; Gareth R. Williams; Sim Wan Annie Bligh (MDPI AG, 2022)
Side-by-side electrospinning is a powerful but challenging technology that can be used to prepare Janus nanofibers for various applications. In this work, cellulose acetate (CA) and polycaprolactone (PCL) were used as polymer carriers for silver nanoparticles (Ag NPs) and lavender oil (LO), respectively, processing these into two-compartment Janus fibers. A bespoke spinneret was used to facilitate the process and prevent the separation of the working fluids. The process of side-by-side electrospinning was recorded with a digital camera, and the morphology and internal structure of the products were characterized by electron microscopy. Clear two-compartment fibers are seen. X-ray diffraction patterns demonstrate silver nanoparticles have been successfully loaded on the CA side, and infrared spectroscopy indicates LO is dispersed on the PCL side. Wetting ability and antibacterial properties of the fibers suggested that PCL-LO//CA-Ag NPs formulation had strong antibacterial activity, performing better than fibers containing only one active component. The PCL-LO//CA-Ag NPs had a 20.08 ± 0.63 mm inhibition zone for E. coli and 19.75 ± 0.96 mm for S. aureus. All the fibers had water contact angels all around 120°, and hence, have suitable hydrophobicity to prevent water ingress into a wound site. Overall, the materials prepared in this work have considerable promise for wound healing applications.